Diagnostic value of MRI-DWI signal intensity value combined with serum PGI, PGII and CA199 in early gastric cancer - Li, Minhong; Zheng, GuangHui; Yu, Lin; Tan, Li-lian; Li, Xi; Li, Min-Jian; Li, Chaowei; Li, Shuxin; Liang, Jiefeng; Zhong, Zhongqi; Li, Zhi Ming (Cellular and Molecular Biology, 2021)
To explore the diagnostic value of MRI-DWI signal intensity value combined with serum PGI. PGII and CA199 in early gastric cancer. Sixty cases of gastric cancer patients admitted to our hospital from December 2019 to December 2020 were selected as the gastric cancer group and 80 cases of healthy volunteers who underwent physical examination in our hospital during the same period were selected as the healthy group. All the 60 patients underwent MRI-DWI examination, and the pathological diagnosis results were regarded as the gold standard. MRI-DWI images, MRI-DWI signal intensity values of patients with different degrees of gastric cancer differentiation. Serum PGI, PGII and CA199 levels of subjects in the two groups were compared. AUC was used to evaluate the diagnostic value of MRI-DWI signal intensity value combined with serum PGI, PG II and CA199 for early gastric cancer. In the healthy group, T1W1 showed relatively uniform low signal intensity. While T2WI showed no significant increase in signal intensity. In the gastric cancer group. There was diffuse gastric wall thickening, local thickening or mass formation; T1WI and WATS showed slightly lower signal intensity in the lesion area. T2WI, FLAIR and B-TFE showed slightly uneven or moderately increased signal intensity. DWI showed limited diffusion, and the signal intensity increased uniformly or more uniformly, and the range of increase was clear. The signal intensity of MRI-DWI was 89.12 ± 8.14 in patients with low differentiation, 82.17 ± 6.35 in patients with moderate differentiation, and 74.52 ± 4.53 in patients with high differentiation. There were significant differences in the signal intensity of MRI-DWI among the three groups, and the difference was statistically significant (F=12.214, P <0.05). Serum PGI levels of subjects in the gastric cancer group were significantly lower than those in the healthy group, and the levels of PGII and CA199 were significantly higher than that in the healthy group, with statistical significance (P <0.05). The AUC, sensitivity and specificity of MRI-DWI signal intensity value and serum PGI, PGII and CA199 combined indexes in the diagnosis of gastric cancer were significantly higher than those of the independent indexes, with statistical significance (P <0.05). Conclusion: MRI-DWI signal strength value, serum PGI, PGII and CA199 levels are closely related to the occurrence and development of early gastric cancer. The combined detection and diagnosis efficiency is higher, which is helpful to improve the detection rate of early gastric cancer and is worthy of extensive clinical application.